Potencialidades e orienta????es para uma maior aproxima????o do Estudo de Impacto Ambiental e a certifica????o Bonsucro das usinas do setor sucroenerg??tico - Sozinho, Davi Wilkson Furtado (2014)
One of the major challenges for humanity in this century is to transition to a future guided in the use of sustainable energy. Biofuels, especially ethanol from sugar cane is being collated as one of the best options for this goal. However, the production of ethanol from sugar cane, is associated with a number of significant environmental impacts, and has been the target of much criticism from the international market. In this sense, there is a need to demonstrate sustainability in the ethanol production chain to ensure that such alternative energy actually meets the requirements of sustainable development. There are various environmental management tools applied to the ethanol production chain, among these, we highlight the Environmental Impact Assessment (EIA) and Environmental Certification. The main objective of this research is to propose guidelines to promote closer ties between the Bonsucro Certification and Environmental Impact Studies applied to the sugarcane industry. The importance of this research lies in the possible future Environmental Impact Assessments (EIAs) sector may include aspects relevant to the environmental certification in sugarcane production chain. The methodology Qualitative Exploratory - Descriptive, through a case study multicase. The data collection instrument used is from reports focal semistructured interview and analyzed the principles of content analysis. The association between environmental management instruments showed that the points of greater dialogue on the content of EIA compared to the principles of certification are facing the issues of soil, water, biodiversity, ecological services and economic growth. The criteria of accreditation Bonsucro that bear no association with EIAs analyzed relate to socioeconomic, primarily related to labor issues, production expertise and qualification of skilled labor and monitoring the efficiency of production and process impacts. This research sees as potential for rapprochement between the EIA and the sugarcane industry Bonsucro enhance and substantiate the approach of social impacts in EIA, impacts mainly focused on labor issues accreditation. In terms of contributions of this research into practice within the professional master's degree, can provide technical guidance for the preparation of environmental impact studies of the sugar-energy sector, especially with regard to environmental impacts and approach in order to obtain the Bonsucro certification; guide the steps of diagnosis, identification and assessment of environmental impacts, as well as the proposition of environmental programs so as to facilitate the achievement of future Bonsucro accreditation during the operation of the business of the sugarcane sector; and encourage investment in the economy of the entire lifecycle of an enterprise's sugarcane industry, as the environmental variable, the appreciation of the potential of environmental management tools ( EIA and certification ) apply.